2011
DOI: 10.1038/ijo.2011.192
|View full text |Cite
|
Sign up to set email alerts
|

Causes and consequences of obesity: the contribution of recent twin studies

Abstract: Obesity is a genetically complex disorder that produces a myriad of health problems. Most of the recognized complications of obesity are not only strongly influenced by lifestyle factors, but also present with independent genetic predispositions that are notoriously difficult to disentangle in humans. Most studies on the causes and consequences of acquired obesity are encumbered by the incomplete ability to control for genetic influences. However, utilizing a unique experiment of nature, namely monozygotic twi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
59
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 67 publications
1
59
0
2
Order By: Relevance
“…The participants were divided in categories according to their BMI (in kg/m 2 ) as follows: normal weight (19 # BMI < 25), overweight (25 # BMI < 30), and obese (BMI $ 30) ( Table 1). Nine twin pairs were concordant (BMI difference <3 kg/m 2 ) and 11 pairs were discordant for BMI (BMI difference $3 kg/m 2 ); a BMI difference of 3 kg/m 2 represented the top 5% most discordant MZ twin pairs (25,27). Eleven of the twin pairs were female and 9 were male.…”
Section: Participants and Methodsmentioning
confidence: 98%
“…The participants were divided in categories according to their BMI (in kg/m 2 ) as follows: normal weight (19 # BMI < 25), overweight (25 # BMI < 30), and obese (BMI $ 30) ( Table 1). Nine twin pairs were concordant (BMI difference <3 kg/m 2 ) and 11 pairs were discordant for BMI (BMI difference $3 kg/m 2 ); a BMI difference of 3 kg/m 2 represented the top 5% most discordant MZ twin pairs (25,27). Eleven of the twin pairs were female and 9 were male.…”
Section: Participants and Methodsmentioning
confidence: 98%
“…Studies in older adults also identified the BCAA-related signature, and reported higher leucine/ isoleucine and valine in obese compared with nonobese individuals (4,(9)(10)(11). Furthermore, experimental research using metabolomic profiling identified causal effects of weight gain on multiple blood metabolites, including elevation of BCAAs, very low-density lipoprotein (8,10,12), triacylglycerol (10), C-reactive protein (8,10), and insulin-like growth factor (10).…”
Section: Significancementioning
confidence: 99%
“…About 75% of the population experiences weight gain during this transition (2, 3), but there have been few efforts to identify biomarkers of risk that could guide prevention efforts. A study (4) in monozygotic twins discordant for body mass index (BMI) reported divergence at about the age of 18 y, corresponding to a time in life when the environment shifts, and further underscoring the importance of young adulthood in the lifetime trajectory of adiposity and as a window of opportunity for prevention (5).…”
mentioning
confidence: 99%
“…The independent genetic predispositions associated with OB are difficult to disentangle in humans. 62 Additionally, OB treatment is mainly based on behavioral approaches. Thus, we are in need of evidence on the environmental aspects of the condition in order to be able to design interventions.…”
mentioning
confidence: 99%